Zalmoxidae (Arachnida: Opiliones: Laniatores) of the Paleotropics: a catalogue of Southeast Asian and Indo-Pacific species - Sharma, Prashant P.; Kury, Adriano B.; Giribet, Gonzalo (Zootaxa, 2011)
A revised catalogue of the Paleotropical Zalmoxidae including images of selected available type specimens is presented. Distribution data are provided to the best of our knowledge. The genera Acrozalmoxis Roewer, 1915, Camanastus Roewer, 1949, Papuastus Roewer, 1949, Savoa Roewer, 1949, and Zalmoxomma Roewer, 1949 are newly synonymized with the type genus Zalmoxis Sørensen, 1886. The following new combinations are established: Zalmoxis australis, Zalmoxis bonka, Zalmoxis insularis, Zalmoxis maculosus, Zalmoxis occidentalis, and Zalmoxis ponapeus. Bogania Forster, 1955 and Bunofagea Lawrence, 1959 are removed from Zalmoxidae and transferred to Phalangodidae. Gjellerupia Roewer, 1913 and Spalicus Roewer, 1949 are considered Grassatores incertae sedis. The incidence of preoccupied taxon names is redressed by designation of new specific epithets as follows: Zalmoxis neoguinensis (Roewer, 1915) is renamed Zalmoxis thorelli; Zalmoxis neoguinensis (Müller, 1917) is renamed Zalmoxis muelleri; Zalmoxis neoguinensis (Roewer, 1949) is renamed Zalmoxis mutus; and Zalmoxis minima (Roewer, 1915) is restored to Gjellerupia minima. Zalmoxis pallicolor Strand, 1910 is synonymized with Zalmoxis armatipes Strand, 1910. Diagnoses of genera are provided. Species richness and familial level relationships of Zalmoxidae are discussed.